Evaluation of attitudes and knowledge of anesthesiologists about regional anesthesia methods in ophthalmic surgery: A national survey study - Gölboyu, Birzat Emre; Çiftçi, Bahadır (Bayrakol Medical Publisher, 2023)
Aim: The use of regional techniques in ophthalmic surgery is becoming increasingly important. Worldwide, these techniques are usually performed by ophthalmologists, while the perioperative care of patients is provided by anesthesiologists. Therefore, good communication between the surgeon and the anesthesiologist is necessary for the careful management of all techniques used in ophthalmic surgery. In this study, the willingness of anesthesiologists to assume responsibility in the use of regional techniques and their knowledge of ophthalmic nerve blocks were assessed in a national survey.Material and Methods: A total of 23 questions were asked to assess attitudes and knowledge about regional anesthesia procedures in ophthalmic surgery, and participants had three weeks to complete the Web-based questionnaire. Complete responses from 126 physicians were analyzed.Results: 60% of participants work in university hospitals as faculty members. Although 54.8% of participants had worked in ophthalmic surgery for 3 months or more, and 76% reported that they had not attended any lectures or seminars on regional block use in ophthalmic surgery. When asked who applied blocks in ophthalmic surgery, 95% of the participants answered the surgical team.Discussion: The lack of theoretical and practical knowledge about ophthalmic nerve blocks is striking even among the group of physicians who practice regional anesthesia. Even if regional techniques are performed by the surgeon himself, the anesthesiologist's responsibility in perioperative patient care cannot be ignored. For this reason, the level of knowledge of anesthesiologists on this topic should be increased through various continuing education courses.
Keywords: Multimodal Pain Management; Ophthalmic Surgery; Regional Anesthesia; Retrobulbar Block; Ophthalmic Block